2016
DOI: 10.3892/ol.2016.5397
|View full text |Cite
|
Sign up to set email alerts
|

ETS-related gene is a novel prognostic factor in childhood acute lymphoblastic leukemia

Abstract: Abstract. The ETS-related gene (ERG) has been demonstrated to be associated with overall survival in cytogenetically normal acute myeloid leukemia and acute T cell-lymphoblastic leukemia (T-ALL) in adult patients. However, there are no data available regarding the impact of ERG expression on childhood ALL. In the present study, ERG expression levels were analyzed in bone marrow samples from 119 ALL pediatric patients. ALL patients demonstrated higher ERG expression compared with the controls (P<0.0001). In add… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Since then, YK-4-279 has been shown to have anti-tumor activity across several solid tumors, like Ewing sarcoma, prostate cancer, neuroblastoma, thyroid cancer, melanoma and lymphoma [11][12][13][14]23,[26][27][28]. Since it is well established that leukemia has deregulated ETS activity [6,8,[15][16][17], we hypothesized that TK216 will be a viable therapeutic candidate for the treatment of children diagnosed with leukemia. The primary objective that we have achieved in this study is the experimental testing of the proof-of-concept, the in vitro anti-tumor activity, and the efficacy of the current ETS inhibitor TK216 for the treatment of pediatric AML and B-ALL.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since then, YK-4-279 has been shown to have anti-tumor activity across several solid tumors, like Ewing sarcoma, prostate cancer, neuroblastoma, thyroid cancer, melanoma and lymphoma [11][12][13][14]23,[26][27][28]. Since it is well established that leukemia has deregulated ETS activity [6,8,[15][16][17], we hypothesized that TK216 will be a viable therapeutic candidate for the treatment of children diagnosed with leukemia. The primary objective that we have achieved in this study is the experimental testing of the proof-of-concept, the in vitro anti-tumor activity, and the efficacy of the current ETS inhibitor TK216 for the treatment of pediatric AML and B-ALL.…”
Section: Discussionmentioning
confidence: 99%
“…In hematological malignancies, the aberrant activity of the ETS factors is frequently observed to result from abnormal ETS expression and chromosomal translocations leading to oncogenic gene fusions [5,6]. Deregulated expression of multiple ETS factors like ERG, FLI1 and SPI1 contribute to the genesis of leukemia and impact the survival outcome in leukemia patients [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Another study found that patients with acute lymphoblastic MPO and ERG, respectively, highlighting granulocytes. All magnifications × 400 leukemia/lymphoma had higher expression of ERG than normal controls, and that lower levels of ERG expression correlated with a T-ALL phenotype and an inferior relapse-free survival rate [21]. However, these studies used gene expression profiling examining DNA copy number alterations by SNP microarrays, and reverse transcription polymerase chain reaction (RT-PCR), respectively, and did not examine ERG expression by IHC analysis.…”
Section: Discussionmentioning
confidence: 99%